Supply Chain Network Design Using Particle Swarm Optimization (PSO) Algorithm - Karami, Danial (International journal of industrial engineering and operational research, 2022)
A supply chain is a complex network which involves the products, services and information flows between suppliers and customers, get the desired combination of low cost and high quality. Cooperating with good strategic partners is the sure way to tackle the potential problems arising from competition. The single-objective supply chain model to find the optimum configuration of a given supply chain problem which minimizes the total cost. There is need for a business model to realize mass customization in the industry. In this paper, we propose the setting method of the optimum order quantity by particle swarm optimization for supply chain management to minimize the combined facility location and shipment costs subject to a requirement that all customer demands be met.